LOGICAL SCALES IMAM AL-GHAZALI (505 AH) AND SOME OF ITS APPLICATIONS TO MATTERS OF BELIEF - MARHON , RAHIM (Islamic Sciences Journal, 2023)
Imam Al-Ghazali, may God have mercy on him, tried to make use of the logical rules to serve the science of belief, and it is no secret that logical measurement is one of the most accurate sections of this science. They are: Equilibrium Balance, which is: Returning the first form of gestational measurement to the Greater Equilibrium Balance, it is divided into three sections (the largest, middle, and smallest balance) and the second balance is the balance of concomitance and this pattern of inference is organized within the framework of the connected conditional measurement that consists of a conditional introduction connected to Zou This is a measure of inference in the framework of a separate conditional measurement, which is unlike the pattern of convergence, and consists of a separate conditional introduction and a local introduction and a local result.